Teaching Technical Technical Vocabularyin Esp - Sadikova Makhbuba Baxtiyarovna; Almardanova Zulfiya Chorievna (Journal of Higher Education and Academic Advancement, 2024)
This article provides information on the use of dictionaries in the process of language learning and increasing vocabulary in technical universities. Today, there are a number of innovative ways to increase vocabulary. This article discusses ways to increase technical vocabulary with the help of dictionaries and its importance.